Analisis Jumlah Kendaraan Yang Melewati Jalan Di Kecamatan Bagan Sinembah Kabupaten Rokan Hilir - Wan Dea Vianda; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bagan Sinembah Subdistrict is one area that has the potential to produce carbon dioxide (CO2) emissions from transportation activities in Rokan Hilir Regency, Riau. This research was conducted to determine CO2 emissions generated from transportation activities for a week. The method used is recording traffic activities to calculate CO2 emissions. The results of the research obtained are, carbon dioxide emissions from transportation activities in the sub-district of the Sinembah chart, namely 18,812,434 tons CO2 / year.Keywords: Carbon Dioxide Emissions, Bagan Sinembah Subdistrict.